The Diversity of Literary Space in Some Nominated and večernica-Awarded Literary Works - Tucovič Sturman, Vladka (Trideset let literarne nagrade večernica, 2026)
The article uses the methodology of spatial literary science to present the diversity of literary space in some of the nominated and awarded works, from the earlier ones (Marjan Tomšič: Katka in Bunkec, Martova velika junaštva; Miroslav Košuta: Njune zgodbe; Marko Kravos: Trst v žepu: pogled na zgodovino od popka dol), which are associated with Primorska, to those whose literary space is nature, more precisely the forest (Jana Bauer: Groznovilca v Hudi hosti, Barbara Simoniti: Močvirniki, Luna J. Šribar: Grizolda in Maček), and the sea or island (Slavko Pregl: Srebro iz modre špilje, Mate Dolenc: Mali princ z otoka, Irena Androjna: Modri otok). It answers the research questions of what literary space represents in selected youth prose, how it is presented or how its representations differ between individual authors and their works, and what meaning or role literary space has in each selected literary work.